1986
DOI: 10.1128/jb.167.3.975-980.1986
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of the gene of a penicillin-binding protein supposed to cause high resistance to beta-lactam antibiotics in Staphylococcus aureus

Abstract: A novel penicillin-binding protein, PBP-2' (Mr about 75,000), is known to be induced in excessively large amount by most beta-lactam compounds in cells of a clinically isolated strain of Staphylococcus aureus, TK784, that is highly resistant to beta-lactams and also most other antibiotics. This protein has very low affinities to most beta-lactam compounds and has been supposed to be the cause of the resistance of the cells to beta-lactams. A 14-kilobase DNA fragment was isolated from the cells that carried the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
192
1
2

Year Published

1991
1991
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(195 citation statements)
references
References 17 publications
0
192
1
2
Order By: Relevance
“…Earlier studies had shown that Mcr S . aureus isolates contain chromosomal DNA, amounting to 30 kb or more, which is also absent from Mcs strains (Beck et al, 1986;Matsuhashi et al, 1986;Matthews et al, 1987). This DNA contains the Mc' determinant mec and determinants for various other resistances (Skinner el al., 1988;Skurray et al, 1988;Ubukata et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies had shown that Mcr S . aureus isolates contain chromosomal DNA, amounting to 30 kb or more, which is also absent from Mcs strains (Beck et al, 1986;Matsuhashi et al, 1986;Matthews et al, 1987). This DNA contains the Mc' determinant mec and determinants for various other resistances (Skinner el al., 1988;Skurray et al, 1988;Ubukata et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…This bacterium is one of the most prevalent microorganisms in nosocomial infections worldwide and methicillin-resistant strains represent 15-45% of all S. aureus isolates (36). MRSA isolates carry the mec gene, a 2130-bp DNA fragment of non-staphylococcal origin encoding a low antibiotic-affinity penicillin-binding protein (37). Since methicillin resistance was first identified in a clinical isolate of S. aureus, its incidence has increased significantly, MRSA has spread globally, and the mec gene has also been detected in several other staphylococcal species (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…MRSA isolates carry the mec gene, a 2130-bp DNA fragment of non-staphylococcal origin encoding a low antibiotic-affinity penicillin-binding protein (37). Since methicillin resistance was first identified in a clinical isolate of S. aureus, its incidence has increased significantly, MRSA has spread globally, and the mec gene has also been detected in several other staphylococcal species (37,38). Specifically, S. aureus growth, including MRSA, was effectively inhibited by compound II and other derivatives, suggesting the applicability of these naphthoquinones against staphylococci.…”
Section: Discussionmentioning
confidence: 99%
“…In 1986, the mecA gene was cloned from a Japanese MRSA strain and its sequence was determined. 32 This gene was found to be widely distributed among S. aureus as well as coagulase negative staphylococci. It was hence speculated that the mec determinant must be freely transmissible among staphylococcal species.…”
Section: Molecular Basis Of Methicillin Resistance In Staphylococcus mentioning
confidence: 99%